Mediating effect of work category on relationship between professional competencies' and decision making among public relations practitioners in governmment - linked companies - Samsudin, Khairul Nizam (2020)
Organizational success can only be achieved when each stakeholders mutually agrees in decision making process in which the decision made will benefit all parties and the organization will be able to operates effectively. For this reason, public relations (PR) plays an important role where the PR practitioners will be the middle person between each stakeholders to ensure that the decisions made will be valuable to the organization and stakeholders. This general objective of the study was to examine the mediating effect of work categories on the relationship between professional competencies and decision making among public relations (PR) practitioners in the government linked companies (GLCs). A survey was conducted and questionnaires were distributed to157 PR practitioners and data were later analyzed using the SEM PLS technique. Results showed that the dimension of work categories do not influence the relationship between professional competency and decision making. Most importance essence was the involvement in decision making process by PR practitioners working in Malaysia’s GLCs can be enhanced or improved through their level of professional competencies. The results supported the role of PR department to be part of the important sub-system in organization. Competencies acquired by PR practitioners were the main resource that can assist organization to survive. Meanwhile, the contribution of this study to the literature lies in its ability to illustrate the importance of PR competencies in influencing the decision-making process in an organization, which later can develop positive thinking among society on PR being one of the recognized and reputable professions.